Evaluation of Some Liver Enzymes in HIV/AIDS Patients on Antiretroviral Therapy in University of Abuja Teaching Hospital, Nigeria - Peter, Abriba Simon; Matthias, Gambe Solomom; Ezekiel, Chindo; Benedo, Osadolor Humphrey (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Hepatoxicity is a major complication and side effect of antiretroviral therapy (ART). Unfortunately, such studies in this area of evaluating the adverse drug reaction of ART on the liver hepatocytes are only few in number in Nigeria. Objective: To determine the levels of some liver enzymes in HIV/AIDS patients on antiretroviral therapy (ART) and as well evaluate their impact on liver hepatocytes. Methods: This is a hospital-based case-control study. A total of 153 subjects were recruited in the study, and they were divided into three groups: the control group (which consist of apparently healthy subjects), the study group 1 (consist of HIV positive subject not on ART), and study group 2 (consist of HIV/AIDS patients on ART). The liver enzymes Alanine amino Transferase (ALT), Asparate amino Transfarase (AST) and Alkaline Phosphatase (ALP) were determined using enzyme linked spectrophotometric assay methods, according to the manufacturer’s specifications. Results: The mean standard deviation (SD) of ALT and AST activity of the study group 1 showed significant differences when compared with that of the control group P<0.001, but the ALP has no significant differences P>0.05. In Study group 2, (HIV/AIDS patients on ART) showed significant differences of P<0.001 in ALT, AST and ALP. Conclusion: Some liver enzymes were elevated in subjects on antiretroviral therapy; this elevation could be due to hepatotoxicity of the (ART) used by the HIV/AIDS patients on the liver hepatocytes. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 126-131